1986
DOI: 10.3109/02713688608995175
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome oxidase activity of Fuchs' endothelial dystrophy

Abstract: The normal human corneal endothelial monolayer maintains stromal water equilibrium and thus, transparency, by means of a pump-leak mechanism. Water leaks into the stroma through non-tight lateral cell junctional complexes and is drawn out by an energy dependent cell membrane ion pump. We investigated the histochemical localization of cytochrome oxidase activity (CO), an important energy-deriving mitochondrial enzyme in dysfunctional corneas with Fuchs' endothelial dystrophy (ED), which is a regionally distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 14 publications
3
8
0
1
Order By: Relevance
“…The downregulated transcripts exceeded the upregulated ones and mitochondrial transcripts accounted for the majority of these downregulated genes. These data were consistent with previous studies that showed decreased mitochondrial and pump site densities in FECD41, 77 and indicates a potential decrease in mitochondrial delivery of an adequate energy source. In addition, a comparison between normal and FECD gene libraries revealed a significant decrease in the expression of bicarbonate transporter-related protein-1.…”
Section: Pathophysiologysupporting
confidence: 93%
See 1 more Smart Citation
“…The downregulated transcripts exceeded the upregulated ones and mitochondrial transcripts accounted for the majority of these downregulated genes. These data were consistent with previous studies that showed decreased mitochondrial and pump site densities in FECD41, 77 and indicates a potential decrease in mitochondrial delivery of an adequate energy source. In addition, a comparison between normal and FECD gene libraries revealed a significant decrease in the expression of bicarbonate transporter-related protein-1.…”
Section: Pathophysiologysupporting
confidence: 93%
“…Mitochondrial DNA damage is known to cause dysfunctional mitochondrial protein synthesis, loss of integrity of inner mitochondrial membrane potential, and apoptotic cell death. Interestingly, older studies by Tuberville et al77 showed decreased numbers of mitochondria and a decline in cytochrome oxidase activity in the mitochondria of edematous FECD corneas. The findings of decreased antioxidant defense and oxidative tissue damage in FECD point to an important etiologic component of dystrophic degeneration seen in FECD.…”
Section: Pathophysiologymentioning
confidence: 97%
“…[52][53][54] Previous studies have revealed that there are decreased numbers of mitochondria in FECD endothelium, and that activity of cytochrome oxidase, the major respiratory chain enzyme, is decreased in the central area of FECD corneal buttons. 55 Based on our studies, these findings are consistent with oxidative stress-induced mtDNA damage that could lead to loss of integrity of inner mitochondrial membrane potential and apoptotic cell death.…”
Section: Discussionsupporting
confidence: 76%
“…et al, 2010). Similarly, earlier studies showed decreased numbers of mitochondria in FECD endothelium and a decrease in cytochrome oxidase, the major respiratory chain enzyme, in the central areas of FECD corneal buttons (Johns, D.R., 1995; Tuberville, A.W. et al, 1986).…”
Section: Fuchs Corneal Endothelial Dystrophysupporting
confidence: 69%